Effects of body mass index and insulin resistance on first-time assisted conception and perinatal outcomes in young polycystic ovary syndrome patients - Guo, Jiayu; Chen, Yuanhui; Jiang, Yilin; Zhang, Cuilian (Frontiers in Endocrinology, 2023)
The objective of the study was to explore the effect of different BMI and IR levels on first assisted conception outcomes and perinatal outcomes in patients with polycystic ovary syndrome (PCOS). This study showed heterogeneity in the clinical presentation of basal hormone levels in patients with different levels of BMI and IR, with hyperandrogenemia being more prominent in overweight combined with insulin resistance. In terms of first assisted conception outcomes, the number of oocytes retrieved, mature oocytes and normal fertilization oocytes were also significantly lower in patients with OW combined with IR, but the number of available embryos and clinical pregnancy rate did not differ significantly, which may be related to the limitations of the retrospective analysis. However, the early pregnancy loss rate was significantly higher in patients with OW combined with IR, and different levels of BMI and IR were independent risk factors for early pregnancy loss rate. Therefore, in clinical practice, it is important to assess the pregnancy outcome of infertile women by integrating multiple indicators in these patients, as well as to give tailored pregnancy guidance and treatment procedures for PCOS patients with varying features.